Experimental and molecular dynamics study of graphene oxide quantum dots interaction with solvents and its aggregation mechanism - Jauja-Ccana V.R. (2021)
This work describes the aggregation process and explains the optical behavior of graphene oxide quantum dots (GOQDs) in different solvents using molecular dynamics, DFT, and experimental observations. The optical behavior of electrochemically synthesized GOQDs in different solvents was analyzed by UV–Vis spectroscopy, and dependence between the spectra and the solvents (water, ethanol, acetone, chloroform, toluene, and n-hexane) was found. Molecular dynamics methods were used to determine that the local structure of the solvent molecules and the nature of intermolecular forces between GOQDs dominate their aggregation state and their optical properties in each solvent. These computational studies based on liquid-liquid systems provide a fast and straightforward approach to develop synthesis and purification methods that allow tailored advanced optical properties of GOQDs. © 2021 Elsevier B.V.